From bodies to bases : human biology and the laws of property - Candlish, John (IIUM Press, 2009)
From Bodies to Bases: Human Biology and the Laws of Property takes the reader through the reactions of legal systems to the creeping commodification of all components of the human body. In a hierarchical approach starting with the whole body, through the organs, tissues, cells, and finally individual molecules such as DNA, the author shows how legislation and judicial decisions attempt to protect human dignity against those who would manufacture human clones, traffic in organs, market blood, eggs and sperm, patent genes, and exploit the genomes of the innocent.